Phytochemical analysis, total flavonoid and phenolic content, antioxidant, and antimicrobial properties of Hypotrachyna cirrhata (Fr.) Divakar - Nirmala Sharma; Deepa Karki; Bhanu Bhakta Neupane; Achyut Adhikari (Bibechana)
Despite being a source of nutrition and ethnomedicinal uses, research on edible lichen Hypotrachyna cirrhata remains limited. This research work reported the antioxidant activity and antibacterial activity of Hypotrachyna cirrhata. The total phenolic content (TPC) and total flavonoid content (TFC) of H. cirrhata were measured as 42.165 ± 0.98 mg GAE/g and 11.789 ± 0.34 mg QE/g, respectively. In this assay, ethyl acetate fraction demonstrated strong antioxidant potential with an IC50 value of 34.14 ± 0.17 µg/mL in in vitro DPPH radical scavenging assay. In contrast, hexane showed a higher IC50 value of 74.3 ± 1.13 µg/mL, compared to the standard quercetin, which had an IC50 value of 62.87 ± 1.02 µg/mL. The methanolic extracts of the lichen demonstrated notable antimicrobial effects against pathogens, with minimum inhibitory concentration (MIC) values recorded at 195.312 μg/mL and minimum bactericidal concentration (MBC) ranging from 195.312 to 390.625 μg/mL. The study suggested that H. cirrhata may exhibit significant levels of total phenolic content (TPC) and total flavonoid content (TFC), which are closely associated with enhanced antibacterial and antioxidant activities.